KEBERPIHAKAN MEDIA MASSA PADA JUDUL PEMBERITAAN KASUS PENEMBAKAN ANGGOTA FPI DI TOL JAKARTA-CIKAMPEK INDONESIA - Rai Bagus Triadi; Neneng Nurjanah (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2022)
As a means of social control, the mass media needs to accurately describe an event to show its independence and credibility. Including, during the shooting incident of an FPI member on the Jakarta-Cikampek toll road, Indonesia in 2020. This event is not only of public concern, but also of language researchers to see how the mass media takes sides. By utilizing qualitative methods and critical discourse analysis initiated by Norman Fairclough, this study focuses on the analysis of the news headlines on the shooting of FPI members on the Jakarta Cikampek Toll Road. Based on the results of the analysis on news text production practices which are realized through titles, it appears that there is a partiality towards one of the parties. Apart from that, in the production of texts, there is also a motivation in the production of texts, namely efforts to create a positive image of certain parties. Keywords: partiality; news title; critical discourse analysis; Norman Fairclough